(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Drugs are a kind of medication that have a wide range of therapeutic applications. Drugs can be classified as illegal in the modern world since they are frequently abused for excessive consumption, which generates addiction. Researchers aimed to address this issue, particularly in Barangay Payatas, Quezon City, Philippines and provided the community with the finest preventative program to increase residents’ and adolescents’ knowledge. The researcher is of the opinion that a nation will be improved by a cohesive community and law- abiding citizens. The purpose of this study is to identify the prevalent issues that Barangay Payatas in Quezon City faces. As researchers, we hope to offer a remedy for the issues related to illegal drugs and drug users. Last but not least, researchers will be aware of the aspects that could have an impact on the nation and community on illegal substances. This chapter presents information from twenty (20) Barangay authorities of Barangay Payatas in Quezon City. And fifty (50) residents who took part in the survey as responders. In accordance with the given research topics, it also provides an analysis and interpretation of the data that has been acquired. This chapter summarized the study’s findings, output, conclusion, and recommendation. Studying the Barangay Payatas Quezon City Drug Prevention Program. Barangay Payatas, Quezon City residents responded. Seventy male and female respondents were surveyed. This study found that most responders are single women aged 17–22 and 23 and older. This study recommended adding drug rehabilitation centers to each barangay and supervising the watch list for drug surrenderers and PWUDS.